Investigating Placental Haemodynamics Using MRI - Hutchinson, George (2023)
Magnetic Resonance Imaging (MRI) has been proven to be a safe and powerful tool for investigating the small scale motion of blood as it moves throughout the human placenta in utero, using techniques such as Diffusion Weighted Imaging (DWI) which have been proven to be sensitive to placental haemodynamics and changes in placental insufficiency. However due to the complexity of the human placenta, and the sensitivity of DWI to flow effects interpreting the results of DWI in utero is challenging, as within a single voxel many haemodynamic features can combine, such as blood percolating across the intervillous space, turbulent blood supplied by the spiral arteries and the fetal circulation within the villous tree network. The direct effect of these processes combining is not obvious, and while DWI has been shown to be sensitive to placental dysfunction it is not always clear how changes in signal reflect changes in structure.